Women's work, men's cultures : overcoming resistance and changing organizational cultures - Rutherford, Sarah [ (Sarah Jane)] (Palgrave Macmillian, 2011)
"The success of diversity programs is dependent on organizational culture change. However, the concept of culture is rarely defined, let alone systematically analyzed to show its impact on gender. Dr. Rutherford brings a sophisticated approach to the diversity discourse,using sociological and psychoanalytical theory to demonstrate the persistence of cultures which marginalize and exclude women in organizational life."--Jacket.